Pedagogical Conditions of Forming Professional Subject of the Future Primary School Teachers: Experimental Grounding - Zhurat, Yuliya (Pedagogical Discourse, 2012)
Experimental study of pedagogical conditions of formation of professional subjectivity of students – future primary school teachers. The article is devoted to the experimental study of subjectivity as an integral quality of primary school teachers, to the xperimental verification of pedagogical conditions of its formation in educational activities in the process of vocational training.